1998
DOI: 10.1097/00000542-199806000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Reflexes during a Combination of Propofol and Fentanyl Anesthesia 

Abstract: Incremental doses of fentanyl depress airway reflex responses in a dose-related manner, except for apnea with laryngospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(90 citation statements)
references
References 13 publications
5
83
1
1
Order By: Relevance
“…Third, no control group was included in this study; however, the stability of the model over a specific time frame has been previously examined in a separate group of children anaesthetised with sevoflurane and exposed to three repeated laryngeal stimulations [19] in a similar manner to those in the present study. The laryngeal and respiratory reflex responses were remarkably constant in successive stimulations and the results were in agreement with the work of Tagaito et al [11], who found no significant differences in the incidence of laryngeal and respiratory reflex responses that could be accredited to repeat stimulation. Given these circumstances, it was felt unnecessary to include a control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Third, no control group was included in this study; however, the stability of the model over a specific time frame has been previously examined in a separate group of children anaesthetised with sevoflurane and exposed to three repeated laryngeal stimulations [19] in a similar manner to those in the present study. The laryngeal and respiratory reflex responses were remarkably constant in successive stimulations and the results were in agreement with the work of Tagaito et al [11], who found no significant differences in the incidence of laryngeal and respiratory reflex responses that could be accredited to repeat stimulation. Given these circumstances, it was felt unnecessary to include a control group.…”
Section: Discussionsupporting
confidence: 92%
“…A clinical model using laryngeal stimulation originally developed in adults [11] and adapted to the paediatric setting was applied as we have done in previous studies [10,14]. This model permits detailed analysis of reflex responses under consistent and safe examination conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal and pharyngeal refl exes are depressed by propofol. These effects are further potentiated by opioids [5,6]. Thus provocation of refl exes due to mechanical stimulation by laryngoscopy are reduced or abolished by combination of propofol and opioids, thus facilitating the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after 3 h and 6 h the AG performance was still slower, though not less accurate, than the CG performance. Propofol, fentanyl, and midazolam suppress the laryngeal and pharyngeal responses, which are crucial to vocalisation [19][20][21]. However, the pharmacokinetic properties of a hypnotic agent seem to exclude such a possibility -propofol disappears from the effectory compartment after several minutes and its metabolites are inactive.…”
Section: Discussionmentioning
confidence: 99%